PERAN SASTRA ARAB DALAM PENGEMBANGAN BUDAYA DAN AGAMA ISLAM: DARI MASA PRA-ISLAM HINGGA ERA MODERN - Rifana, Niko (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
This article explores the role of Arabic literature in the development of Islamic culture and religion, from the pre-Islamic era to the modern age. Through the analysis of various Arabic literary works, this article reveals how Arabic literature has served as a crucial medium for disseminating Islamic teachings and shaping the religious identity of Muslims across the world. Arabic literature functions not only as an aesthetic expression but also as a tool to preserve and strengthen Islamic values in the face of modernity's challenges. The article also discusses the influence of Arabic literature in regions such as Andalusia, Persia, and Southeast Asia, and how this literature has adapted to social and cultural changes without losing its inherent Islamic identity.